Linkages between selected hydrological ecosystem services and land use changes, as indicated by hydrological responses : a case study on the Mpushini/Mkhondeni Catchments, South Africa. - Schütte, Stefanie. (2014)
Nature provides essential services to humans, including climate regulation, water provisioning and regulation. These so-called ecosystem services have economical, societal and environmental value. This research aims at improving the knowledge on the linkages between selected hydrological ecosystem services and current and proposed land uses within the water-limited Mpushini/Mkhondeni Catchments in South Africa. The research contributes to the recognition of feedback and linkages within the complex ecological-human system, so that informed land use decisions can be made. The research aim is achieved by first reviewing the literature on hydrological ecosystem services, land use in an ecosystem services context and the links between the two. The study area is then sub-delineated into land use determined hydrological response units for baseline natural land cover, as well as for current and proposed land use scenarios. Using an appropriate model, selected hydrological processes are simulated in order to isolate the effects of individual land uses on hydrological responses, both on a local and a more catchment-wide scale. Various land uses were found to affect hydrological responses, such as runoff and its components of stormflows and baseflows, as well as transpiration and sediment yields, differently. These responses were found to be suitable indicators of selected ecosystem services such as water provisioning or flow regulation. Irrigation and high biomass crops, such as sugarcane and wattle plantations were found to reduce downstream water provisioning services. Degraded lands were found to reduce physical water quality through increased sediment yield, to reduce water provisioning during low flow periods, while the degraded lands increased stormflows, thereby reducing regulation of high flows. Urban land uses were found to significantly increase runoff, with increased impervious areas causing a shift from evaporation and transpiration towards runoff. Stormflows increased, with high flow regulation being reduced. Baseflows increased as well, as a result of a spill-over of runoff from impervious to pervious urban areas, which led to increased low flow regulation. In addition, in this study area urban return flows are generated from externally sourced water, further increasing streamflows and especially low flows. While urban areas showed an increase in downstream water quantity provision, the water quality was reduced. The combined effects of the current land use mosaic on the annual streamflows partially cancel each other out, while the proposed urbanisation dominated hydrological responses. Influences of various land uses on hydrological ecosystem services were thereby shown, which contributes to a better understanding of the linkages between the two. === Thesis (M.Sc.)-University of KwaZulu-Natal, Pietermaritzburg, 2014.